Level markers of bone remodeling in patients with primary hypothyroidism - Chornii, A.; Shmanko, V. (Journal of Education, Health and Sport, 2017)
In the article the research results of biochemical markers of bone metabolism in patients with primary hypothyroidism. It is proved that the people on the background of primary hypothyroidism, periodontal disease is accompanied by a pronounced decline in remodeling processes in bone tissue alveolar process of the jaws.